2014
DOI: 10.3109/14756366.2014.908291
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic thermodynamics of sulfonamide inhibitor binding to human carbonic anhydrases I and II

Abstract: Human carbonic anhydrase (CA) I and II are cytosolic proteins, where their expression disorders can cause diseases such as glaucoma, edema, epilepsy or cancer. There are numerous inhibitors that target these isozymes, but it is difficult to design compounds that could bind to one of these proteins specifically. The binding of sulfonamide inhibitor to a CA is linked to several protonation reactions, namely, deprotonation of the sulfonamide group, protonation of the active site zinc hydroxide and the compensatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 28 publications
5
21
0
Order By: Relevance
“…As the p K a and Δ b‐proton_sulf H values of the compounds did not significantly depend on the nature of the para substituent, we did not measure these values for the compounds of series 1 and 9 bearing a phenyl group at the end of para “tail”, and the average values were used for the calculation of intrinsic thermodynamic parameters. The Δ C p values of compound sulfonamide group protonation were positive, as previously determined for compounds such as acetazolamide (AZM) …”
Section: Resultssupporting
confidence: 57%
“…As the p K a and Δ b‐proton_sulf H values of the compounds did not significantly depend on the nature of the para substituent, we did not measure these values for the compounds of series 1 and 9 bearing a phenyl group at the end of para “tail”, and the average values were used for the calculation of intrinsic thermodynamic parameters. The Δ C p values of compound sulfonamide group protonation were positive, as previously determined for compounds such as acetazolamide (AZM) …”
Section: Resultssupporting
confidence: 57%
“…The pK a and enthalpies of active site hydroxide protonation could be compared to other CA isoforms ( Table 2). The CA I had a pKa 8.4, CA II-7.1 [53], CA XIII-8.3 [50], CA XII-7.0 [51], and for CA VB the pK a was 7.2. The increase in pK a for CA I and CA XIII was largely due to the more exothermic enthalpy of protonation (-41 and -44 kJ mol -1 , respectively) as compared to other CAs (* -30 kJ mol -1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The standard error of the K d measurements is approximately 1.69 of the K d value isoforms [50][51][52][53][54] and are explained by the binding-linked protonation equilibria. First, a sulfonamide compound has to undergo deprotonation in order to bind to the Zn in the active center of the enzyme.…”
Section: Inhibitor Binding To Ca Vb By Itcmentioning
confidence: 98%
“…, the observed enthalpies of binding are essentially useless in the analysis because they are greatly dependent on buffer and pH. Therefore, it is even more important to distinguish intrinsic enthalpies and entropies from the observed values .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it has been used to determine the binding of only some inhibitors while most were determined by FTSA which is a rapid screening method . In this study, the observed and intrinsic binding are distinguished by subtracting the linked protonation events occurring in conjunction with the binding reaction between the protein and the ligand . Intrinsic thermodynamic profiles are important to determine the molecular recognition between the protein and the ligand and thus for the design of new compounds with desired affinity properties.…”
Section: Introductionmentioning
confidence: 99%